Ammatoa's inheritance law system - Hiksyani Nur Khadijah; Aan Aswari (Indonesia Prime, 2019)
Indigenous peoples influence the diversity of inheritance in Indonesia, so there is sometimes a dualism of the immature inheritance that can lead to conflict, but the indigenous community Ammatoa Kajang District of South Sulawesi consisting of community groups Ilalang Embayya and embayya Ipantarang remained effective in running their customary inheritance according to instructions from the leader of Ammatoa bohe ' amma based on Turie ' Akra'kna. This article aims to suggest that the traditional inheritance law of Ammatoa, in addition to other positive law can run effectively without any dispute in the middle of Ammatoa society, in addition to this article also aims to demonstrate that the simple way of life of citizens can reduce conflict among indigenous peoples. Results indicate the ability factor of heirs, and the need for heirs resulted in the distribution of inheritance during the Ammatoa society without having to wait for the death of the heir first, the division is governed by Install ri Kajang which was applied by the customary leader assisted by his representatives. Finally, this article concluded that the consistency of the concept of kamase-Masea in life brings their lives in a state of order and tranquility and has been going on a hereditary basis, due to the restriction of community needs maintained by Bohe ' Amma is the concept of Ammatoa society, so that they reject the development comes from the attention of the Government that can give rise to a complex and complicated legal system